Rekonstruksi Moral bagi Mahasiswa dalam Pendidikan Islam di Era Society 5.0. : Moral Reconstruction For Students In Islamic Education In The Era Society 5.0 - Intan, Nabila; Fitri, Ayu Laila; Assegaf, Abd. Rachman (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2025)
The moral reconstruction of students in Islamic education is to emphasize the necessity and importance of Islamic education in Indonesia. This arrangement and rearrangement is intended so that Islamic education both institutions and learning materials. Even education in the era of society 5.0, allows students in learning activities side by side with technology. Disruption in the world of education, especially in Islamic education, is inevitable. Thus, activists and education stakeholders get an overview of the urgency of the presence of technology in the era of society 5.0 in the world of Islamic education in particular. The research approach is qualitative and this research method used is a literature review the method used is descriptive analysis by collecting data through written literature in the form of books, scientific journals as the main source which is used to describe the reconstruction of Islamic education in the era of society 5.0.